2015
DOI: 10.1111/cas.12703
|View full text |Cite|
|
Sign up to set email alerts
|

Atonal homolog 1 protein stabilized by tumor necrosis factor α induces high malignant potential in colon cancer cell line

Abstract: Patients with inflammatory bowel disease (IBD) have an increased risk of developing colitis-associated colorectal cancer (CAC). CAC cells often develop chemoresistance, resulting in a poorer prognosis than that of sporadic colorectal cancer (CRC). The mechanism by which CAC enhances malignant potential remains unknown. We have previously reported that the proteasomal degradation of the transcription factor Atonal homolog 1 (Atoh1) protein results in the non-mucinous form of CRC. It also remains unknown whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Depending on the cellular context, ATOH1, also known as Math1 and Hath1, may function both as an oncogene, for example, in medulloblastoma (Briggs et al, 2008;Grausam et al, 2017) or as a tumor suppressor gene, for example, in colon (Bossuyt et al, 2009;Fukushima et al, 2015), gastric (Han et al, 2015), and hepatocellular cancer (Gao et al, 2017). Despite its high expression in MCC tissues and in classical MCC cell lines (Gambichler et al, 2017), knockdown of ATOH1 did not affect cell viability or proliferation of MCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cellular context, ATOH1, also known as Math1 and Hath1, may function both as an oncogene, for example, in medulloblastoma (Briggs et al, 2008;Grausam et al, 2017) or as a tumor suppressor gene, for example, in colon (Bossuyt et al, 2009;Fukushima et al, 2015), gastric (Han et al, 2015), and hepatocellular cancer (Gao et al, 2017). Despite its high expression in MCC tissues and in classical MCC cell lines (Gambichler et al, 2017), knockdown of ATOH1 did not affect cell viability or proliferation of MCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…IECspecific deletion of IKKb, a key molecule in the NF-jB pathway, reduced the incidence of colitis-induced tumorigenesis, suggesting that IEC-intrinsic NF-jB activation is a major regulator of CAC [88]. Recent studies have suggested that TNF-a may also induce constitutive expression of the transcription factor ATOH1, and direct tumor cells to acquire highly proliferative, and invasive character [89,90]. Also, loss of the gp130-STAT3 axis in IECs reduces the growth and multiplicity of colitis-induced tumors [91].…”
Section: Colitis-associated Cancer Represents Another Aspect Of Iec-dmentioning
confidence: 99%
“…The lentivirus generated from Lenti-CRISPR v2 vector with target array were infected to LS174T cells as described previously (11). As a negative control, LS174T TP53WT cells were generated by infection with the Lenti-CRISPR v2 vector lacking the target array such that these cells would also constitutively express Cas9.…”
Section: Crispr-cas9-mediated Mutagenesismentioning
confidence: 99%
“…Total RNA was isolated using an RNeasy Micro Kit (Qiagen) according to the manufacturer's instructions. cDNA synthesis was performed as described previously (11). One microliter of cDNA was amplified using a QuantiTect SYBR Green PCR Kit (Qiagen) in a reaction volume of 20 mL.…”
Section: Qrt-pcrmentioning
confidence: 99%